Inactivation of Ebola virus and Middle East respiratory syndrome coronavirus in platelet concentrates and plasma by ultraviolet C light and methylene blue plus visible light, respectively. Issue 9 (6th May 2018) - Eickmann, Markus; Gravemann, Ute; Handke, Wiebke; Tolksdorf, Frank; Reichenberg, Stefan; Müller, Thomas H.; Seltsam, Axel
Abstract : BACKGROUND: Ebola virus (EBOV) and Middle East respiratory syndrome coronavirus (MERS‐CoV) have been identified as potential threats to blood safety. This study investigated the efficacy of the THERAFLEX UV‐Platelets and THERAFLEX MB‐Plasma pathogen inactivation systems to inactivate EBOV and MERS‐CoV in platelet concentrates (PCs) and plasma, respectively. STUDY DESIGN AND METHODS: PCs and plasma were spiked with high titers of cell culture–derived EBOV and MERS‐CoV, treated with various light doses of ultraviolet C (UVC; THERAFLEX UV‐Platelets) or methylene blue (MB) plus visible light (MB/light; THERAFLEX MB‐Plasma), and assessed for residual viral infectivity. RESULTS: UVC reduced EBOV (≥4.5 log) and MERS‐CoV (≥3.7 log) infectivity in PCs to the limit of detection, and MB/light decreased EBOV (≥4.6 log) and MERS‐CoV (≥3.3 log) titers in plasma to nondetectable levels. CONCLUSIONS: Both THERAFLEX UV‐Platelets (UVC) and THERAFLEX MB‐Plasma (MB/light) effectively reduce EBOV and MERS‐CoV infectivity in platelets and plasma, respectively.